INTEGRAL EVALUATION OF THE ECONOMIC ACTIVITY, EMPLOYMENT AND UNEMPLOYMENT IN THE REGIONS OF BULGARIA - Y. Hristoskov (Trakia Journal of Sciences)
The purpose of this article is to identify the trends and territorial differences in the economic activity, employment and unemployment, and on this grounds to recommend solutions for overcoming or reduction of the severity of the issues. The study explores the condition and disparities in the labor potential of the regions in the context of the acknowledged and ever deepening demographic crisis in Bulgaria. The object of analysis is the dynamics of the economic activity, employment and unemployment at national and regional level, represented by one summarizing indicator. The integral indicator Economically Active and Employed Population (EAEP), developed by the author, is applied in order to trace the dynamics at national level and to assess the implementation of the set national employment targets under the Europe 2020 program. A modified version of this indicator (EAEP(m)) is also applied, in order to assess the territorial fluctuations in the economic activity, employment and unemployment at the NUTS-2 level. The values of this indicator obtained for each region are compared to already previously set benchmarks. On this basis, the risk regions are identified and solutions are proposed to reduce the problems.